2002
DOI: 10.1093/hmg/11.15.1743
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an imprinted antisense RNA (MESTIT1) in the human MEST locus on chromosome 7q32

Abstract: Imprinted gene(s) on human chromosome 7 are thought to be involved in Russell-Silver syndrome (RSS), based on the fact that approximately 10% of patients have maternal uniparental disomy of chromosome 7. However, involvement of the known imprinted genes (GRB10 at 7p12, PEG10 at 7q21.3 and MEST at 7q32) in RSS has yet to be established. To screen for new imprinted genes, we are initially using somatic cell hybrids containing a paternal or maternal human chromosome 7. Transcripts located between D7S530 and D7S64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 49 publications
1
44
1
Order By: Relevance
“…A role for noncoding RNAs is implicated in the regulation of imprinted genes due to the preponderance of these transcribed sequences located in imprinted domains and empirical data suggesting their importance (26,27,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). For example, the genes Delta, Drosophila homologue-like 1 (DLK1) and maternally expressed gene 3 (MEG3) in the imprinted domain on human chromosome 14 bear remarkable similarity to the IGF2/H19 domain in terms of the genomic organization and putative regulatory features (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…A role for noncoding RNAs is implicated in the regulation of imprinted genes due to the preponderance of these transcribed sequences located in imprinted domains and empirical data suggesting their importance (26,27,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). For example, the genes Delta, Drosophila homologue-like 1 (DLK1) and maternally expressed gene 3 (MEG3) in the imprinted domain on human chromosome 14 bear remarkable similarity to the IGF2/H19 domain in terms of the genomic organization and putative regulatory features (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…PEG10 is identified on human chromosome 7q21 (21,53). Mouse homolog PEG10 has recently been located in a large imprinted gene cluster on mouse proximal chromosome 6 and has been confirmed to be imprinted (54).…”
Section: Discussionmentioning
confidence: 99%
“…13,16,37,47 Isoform 2 has been observed to be preferentially paternally expressed in foetal placenta in other studies, and also in kidney and fibroblast lines, with polymorphic imprinting observed between different fibroblast lines. 48 Variable imprinting of MEST, including that of isoform 2, has also been reported between humanembryonic stem cell (hESCs) lines, raising concerns of the epigenetic stability of these cells. 40,49,50 In view of the observations of aberrant MEST methylation and imprinting with disease, 13,14,16 we considered it important to further characterise expression at the MEST locus in the embryos with expression arising from both alleles.…”
Section: Discussionmentioning
confidence: 99%